Resource rents and economic growth: Governance and infrastructure thresholds - Simplice Asongu; Samba Diop (African Governance and Development Institute (AGDI), 2022)
This study investigates how governance and infrastructure modulate the effect of natural resource rents on economic growth in a sample of 110 countries for the period 2000-2018. The empirical evidence is based on Panel Smooth Transition Regressions (PSTR). The following findings are established. First, the nexus between economic growth and natural resources is not linear and the underlying non-linearity is contingent on existing infrastructural and governance levels. Second, evidence of a "natural resource curse" is apparent in countries with extremely low levels of governance and infrastructural development. Third, the favorable effect of natural resources on economic growth requires a governance threshold of -1.210 and an infrastructure threshold of 2.583 indicating that countries with governance and infrastructure level higher than these values tend to benefit much more from the wealth of natural resources. With high levels of the transition variables (governance and infrastructure), the established thresholds are low and situated between the 5 th and the 10th percentiles. Countries identified below the established thresholds are mainly from Africa. Policy implications are discussed with specific emphasis on African countries.
Keywords: H10; Q20; Q30; O11; O55; 330; Natural Resources; Economic Growth; Governance; Infrastructure; Threshold